Case Study in 21st Century Ecotoxicology: Using In Vitro Aromatase Inhibition Data to Predict Short‐Term In Vivo Responses in Adult Female Fish. (10th March 2021) - Villeneuve, Daniel L.; Blackwell, Brett R.; Cavallin, Jenna E.; Cheng, Wan‐Yun; Feifarek, David J.; Jensen, Kathleen M.; Kahl, Michael W.; Milsk, Rebecca Y.; Poole, Shane T.; Randolph, Eric C.; Saari, Travis W.; Ankley, Gerald T.
Abstract: The present study evaluated whether in vitro measures of aromatase inhibition as inputs into a quantitative adverse outcome pathway (qAOP) construct could effectively predict in vivo effects on 17β‐estradiol (E2) and vitellogenin (VTG) concentrations in female fathead minnows. Five chemicals identified as aromatase inhibitors in mammalian‐based ToxCast assays were screened for their ability to inhibit fathead minnow aromatase in vitro. Female fathead minnows were then exposed to 3 of those chemicals: letrozole, epoxiconazole, and imazalil in concentration–response (5 concentrations plus control) for 24 h. Consistent with AOP‐based expectations, all 3 chemicals caused significant reductions in plasma E2 and hepatic VTG transcription. Characteristic compensatory upregulation of aromatase and follicle‐stimulating hormone receptor (fshr) transcripts in the ovary were observed for letrozole but not for the other 2 compounds. Considering the overall patterns of concentration–response and temporal concordance among endpoints, data from the in vivo experiments strengthen confidence in the qualitative relationships outlined by the AOP. Quantitatively, the qAOP model provided predictions that fell within the standard error of measured data for letrozole but not for imazalil and epoxiconazole. However, the inclusion of measured plasma concentrations of the test chemicals as inputs improved model predictions, with all predictions falling within the range of measured values. Results highlight both the utility and limitations of the qAOP and its potential use in 21st century ecotoxicology. Environ Toxicol Chem 2021;40:1155–1170. © 2020 SETAC. This article has been contributed to by US Government employees and their work is in the public domain in the USA. Abstract :